Akulturasi budaya Tembang Lir-ilir sebagai media dakwah Sunan Kalijaga - Rori Amelya Rumpaka; Lutfiah Ayundasari (Jurnal Integrasi dan Harmoni Inovatif Ilmu-Ilmu Sosial (JIHI3S), 2021)
Islam is mostly embraced by Indonesians. The majority of Indonesians adhere to the largest religion in the world. Islam entered the archipelago through peaceful channels in accordance with the religious mission, namely rahmatan li al-'ālamīn. Which is Islam as a religion that embraces or protects all people and other things. Likewise with the culture in Indonesia. Indonesian culture has existed since time immemorial. Various cultures passed on from their ancestors to their successors. Indonesia has a variety of cultural features that need to be preserved and maintained. This is what makes Indonesian society thick with culture. Islam entering Indonesian territory is not easy. Because the majority of people still adhere to and are thick with culture. Therefore, the figures who spread the religion of Islam must know the character of Indonesian society. Using the method of acculturating existing cultures in Indonesia with Islamic religious values is the right way to spread Islam. Agama Islam dianut sebagian besar oleh masyarakat Indonesia. Mayoritas masyarakat Indonesia menganut agama yang dianut terbesar di dunia ini. Islam masuk ke wilayah Nusantara melalui jalur damai sesuai dengan misi agama yakni rahmatan li al-‘ālamīn. Yang mana Islam sebagai agama yang merangkul atau mengayomi semua umat dan hal lainnya. Begitu pula dengan kebudayaan yang ada di Indonesia. Kebudayaan Indonesia sudah ada sejak dahulu kala. Beragam kebudayaan diwariskan para leluhur kepada penerusnya. Indonesia memiliki beragam corak kebudayaan yang perlu dilestarikan dan dijaga keberadaannya. Hal tersebut yang menjadikan masyarakat Indonesia kental akan budaya. Agama Islam masuk ke wilayah Indonesia tidak mudah. Dikarenakan mayoritas masyarakat masih menganut dan kental akan budaya. Maka dari itu, para tokoh penyebar agama Islam harus mengetahui karakter masyarakat Indonesia. Menggunakan cara mengakulturasi budaya yang ada di Indonesia dengan nilai-nilai agama Islam merupakan cara yang tepat untuk penyebaran agama Islam.